Rethinking Ethical Journalism in the Worsening Socio-Economic and Political Crisis in Zimbabwe. Issue 2 (2nd April 2020) - Mathe, Limukani
Abstract: This article reviews the practice of ethical journalism in Zimbabwe. It reports on a study that engaged with both public and private journalists through in-depth interviews, to rethink ethical journalism in the worsening socio-economic and political situation in Zimbabwe. The study used thematic analysis informed by the communal approach or sociology of journalism ethics to analyse journalists' perspectives. Several factors were found to be causes for unethical journalism practice, namely, political interference; poor economy; corruption; biased editorial policies; political activism; and interests of media owners or funders. The findings of the study reflect parallelism or antagonism between the public and private media in Zimbabwe. Therefore, the article calls for a common view based on the communal approach. It argues that social responsibility must be the norm in the face of corruption and economic challenges. An independent media body should be appointed by the Zimbabwean government to preside over the public media as the first step towards ethical journalism.